The Role of Local Governments in Conservation of Endemic Species: Case of Taurus Frog (Rana Holtzi) - E., Karataş; A, Karataş (International Journal of Scientific Research and Management (IJSRM), 2017)
All living and non-living things are encompassed by the environment. Local governments play importantrole in conservation of environment. It is the responsibility of local governments to ensure a safe andlivable environment for all living things. However, some living species have come to the point ofextinction as a result of some people's unconscious behaviors. One of these living species is the TaurusFrog living in Taurus Mountains in Niğde City of Turkey. This study emphasizes the role and importanceof local governments in conservation of the Taurus Frog (Rana Holtzi), one of endemic species.